2020
DOI: 10.1007/s12529-020-09944-y
|View full text |Cite
|
Sign up to set email alerts
|

Stay Present with Your Phone: A Systematic Review and Standardized Rating of Mindfulness Apps in European App Stores

Abstract: Background Mindfulness-based interventions show positive effects on physical and mental health. For a better integration of mindfulness techniques in daily life, the use of apps may be promising. However, only a few studies have examined the quality of mindfulness apps using a validated standardized instrument. This review aims to evaluate the content, quality, and privacy features of mindfulness-focused apps from European commercial app stores. Methods An automated search engine (webcrawler) was used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 78 publications
(113 reference statements)
7
32
0
1
Order By: Relevance
“…No randomized controlled trial evaluating the effectiveness of one of the included apps could be identified. This lack of a solid evidence base for the use of health apps is in line with that reported in other systematic reviews of app quality (eg, older adults, mindfulness, depression, rheumatoid arthritis, and posttraumatic stress disorder) [36][37][38][39][40]. These systematic reviews showed that the proportion of the scientifically evaluated apps ranges between 0% and 4.8%.…”
Section: Principal Findingssupporting
confidence: 78%
See 1 more Smart Citation
“…No randomized controlled trial evaluating the effectiveness of one of the included apps could be identified. This lack of a solid evidence base for the use of health apps is in line with that reported in other systematic reviews of app quality (eg, older adults, mindfulness, depression, rheumatoid arthritis, and posttraumatic stress disorder) [36][37][38][39][40]. These systematic reviews showed that the proportion of the scientifically evaluated apps ranges between 0% and 4.8%.…”
Section: Principal Findingssupporting
confidence: 78%
“…To determine relevant predictors for overall quality, exploratory multiple linear regression analysis was conducted. Price, store, and the number of functions were used as predictors, as they were significant predictors in other systematic app reviews (eg, older adults, mindfulness, depression, posttraumatic stress disorder, rheumatoid arthritis) [36][37][38][39][40]. Dichotomous predictors were dummy coded.…”
Section: Discussionmentioning
confidence: 99%
“…Our quality ratings are in line with the results of previous systematic evaluations deploying the same rating scales on apps for various health conditions and application areas (e.g., depression, PTSD, pain, rheumatism, physical activity, weight management [ 16 , 36 , 38 , 44 46 , 52 54 ]), all indicating medium overall app qualities with the MARS and ENLIGHT scales. In our study, the categories with the highest ratings were aesthetics and functionality (M = 3.78; M = 3.81), followed by information quality (M = 3.42) and engagement (M = 3.34).…”
Section: Discussionsupporting
confidence: 85%
“…from the stores. The functionality and validity of the program has been proven in previous studies [ 44 46 ]. For further technical details please see [ 47 ].…”
Section: Methodsmentioning
confidence: 94%
“…Suicidal behavior and NSSI-related search terms were identified according to the respective relevant literature (for the complete search term, see Appendix A). The chosen search terms were used to screen the European Apple App Store and Google Play Store systematically for potentially relevant MHA using the automatic search engine of the Mobile Health App Database (MHAD; http://mhad.science) project ( 28), whose functionality and validity have been proven in previous studies (29)(30)(31). The search was conducted in August 2020 with equivalent search terms for suicidal thoughts and behavior in German, English, Dutch, and Spanish languages and for NSSI in German and English languages.…”
Section: Search Strategy and Selection Proceduresmentioning
confidence: 99%